(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article outlines the general state of research on Academician Boriboy Akhmedov and assesses the place of his scholarly legacy in contemporary historiography. The relevant literature is classified into two groups: biographical and memoir-based publications, and studies that rely on Ahmedov’s works as a major scholarly foundation. Works produced in the Soviet period, the years of independence, and abroad are reviewed comparatively, and major methodological and bibliographic issues are noted in general terms. The paper also briefly summarizes how Ahmedov’s contributions to ethnogenesis, source studies, and Timurid studies have been interpreted in subsequent scholarship. The conclusion emphasizes the continuing need for a comprehensive and systematic study of Ahmedov’s life and academic career, including a focused analysis of his methodology and principles of working with sources.